(Un)civil War: The Current Political Discourse in America (In Factis Pax: Journal of Peace Education and Social Justice, 2018)
Although negative campaigning and mean-spirited politics are farfrom new, the venomous way in which political candidates and officers behave toward those in the opposing party, and even sometimes within their party, has seemingly hit a zenith with the presidential election of Donald Trump. Not only did candidate and now-President Trump take vitriolic rhetoric to a new level, but there is evidence to suggest that his campaign and election has given others license to spew hateful comments about those with whom they disagree. Importantly, though, the political Left also struggles with incivility. Even a perfunctory review of political discourse within the Left reveals that this incivility is not only directed at the Right, but also at others who align on the Left but whose positions are different. This paper explores the divisiveness of political incivility on the Right and the Left, framing it as a natural but disturbing consequence of neoliberal ideology that is hyper-focused on individuals and winning at all costs. The paper concludes with recommendations for improving political discourse, drawing on the work of Lilliana Mason (2018) in her book Uncivil Agreement: How Politics Became Our Identity.